5c+3-4c=-26+14

Simple and best practice solution for 5c+3-4c=-26+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5c+3-4c=-26+14 equation:


Simplifying
5c + 3 + -4c = -26 + 14

Reorder the terms:
3 + 5c + -4c = -26 + 14

Combine like terms: 5c + -4c = 1c
3 + 1c = -26 + 14

Combine like terms: -26 + 14 = -12
3 + 1c = -12

Solving
3 + 1c = -12

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 1c = -12 + -3

Combine like terms: 3 + -3 = 0
0 + 1c = -12 + -3
1c = -12 + -3

Combine like terms: -12 + -3 = -15
1c = -15

Divide each side by '1'.
c = -15

Simplifying
c = -15

See similar equations:

| 5x^2+5x-20=0 | | 3.00*x+5=50 | | p=a+5+c | | 2-3i/3+2i | | 14=(3)(3)+x | | p=220/0.04(2) | | 2x+3(x+5)=130 | | 5x-x-18-4x=-36 | | 75/8=11/4v+7/2v | | (8m+6)+(-5m-6)= | | 2x-3/2x=7/10 | | 16x-3(4x+7)=6x+(2x+21) | | 16x-3(4x+7)=6x(2x+21) | | -6x+5(5x+1)=119 | | Y=10-2(5)/2X | | Y=10-2(5)/2 | | 12x^-4y^2/3x^2y^-4 | | 90+84+2x+68+2x+118=360 | | x^2/9x | | 5x+50-4x-16=x+8 | | -3v-13=4v+8 | | 5x^2+25x+5=0 | | A+1/3=14 | | 5(t-4)+7t=6(2t+3)-12 | | 7/4=x+3/5 | | 13x+2=105 | | R-2=-157/8 | | 2u+6=6u+5 | | 90+84+2x+118+2x+68=360 | | =(7k+5)+9k | | ((3w-8)/7)+((7w-2)/3)=12 | | 12.05x=6+x |

Equations solver categories